Experimental and numerical investigation on slug initiation and initial development behavior in hilly-terrain pipeline at a low superficial liquid velocity. (April 2018) - Yin, Pengbo; Cao, Xuewen; Li, Yuhao; Yang, Wen; Bian, Jiang
Highlights: Slug flow experiments at a low liquid velocity in hilly-terrain pipeline are conducted. A numerical simulation model is proposed for slug flow prediction. The slug initiation mechanisms around the elbow are discussed. Pressure drop and liquid holdup signals are presented for slug flow description. Abstract: The initiation and initial development behavior of gas–liquid slug flow is experimentally and numerically investigated in a hilly–terrain pipeline at a low superficial liquid velocity. The test section consists of three parts: three sections of horizontal pipe, one ascending pipe, and one descending pipe. The inclined pipes are at an angle of 10°, all sections are connected by elbow pipes, and the inner diameter is 40 mm. Air and water, with a superficial liquid velocity ranging from 0.002 m/s to 0.1 m/s, are used as working fluids, which are operated at ambient temperature and pressure. Differential pressure transmitters and ultrasound Doppler velocimetry are used to measure the pressure drop and liquid film height, and velocity, respectively. Numerical simulation is simultaneously carried out using the coupled level-set and volume of fluid method, and is verified through comparison with experimental data. Slug initiation mechanisms are discussed based on experimental observation and numerical prediction. The characteristics of liquid slug initiation and initial development are also explained using pressure drop fluctuation, liquid holdup, and phase distribution features. The overall qualitative and quantitative analysis can contribute to the improvement of recent theoretical and numerical models.